“Nothing is ever going to change if we don't start advocating for our child.”: Community-level disclosure and stigma management strategies among parents of internationally adopted children living with PHIV - Bingaman, Amanda; Hamilton, Alison; Houpt, Bethany; Olivero, Rosemary; Fair, Cynthia (Frontiers in Public Health, 2023)
Background The number of internationally adopted children living with perinatally-acquired HIV (IACP) in the U.S. is increasing, yet little is known about their families' experiences navigating HIV disclosure within a community context. This paper examines the lived experiences of adoptive parents as they navigate HIV disclosure and manage stigma toward their adopted children within their broader communities. Methods A purposive sample of parents of IACP was recruited at two pediatric infectious disease clinics and via closed Facebook groups. Parents completed two semi-structured interviews approximately one year apart. Interview questions included strategies parents used to reduce the impact of community level stigma that their child is likely to encounter as they mature. Interviews were analyzed using Sort and Sift, Think and Shift analytic approach. All parents (n = 24) identified as white and most (n = 17) had interracial families, with children adopted from 11 different countries (range: age at adoption 1-15 years; range: age at first interview 2-19 years). Results Analyses revealed that parents serve as advocates for their child by both supporting more public HIV disclosure at times, but also applying indirect strategies such as working to improve outdated sex education material. Knowledge of HIV disclosure laws empowered parents to make informed decisions about who, if anyone, in the community needed to know their child's HIV status. Conclusion Families with IACP would benefit from HIV disclosure support/training and community-based HIV stigma reduction interventions.